KEBASYARIYYAHAN DAN KEMA’SUMAN RASULULLAH PERSPEKTIF AL-QUR’AN - Masykur, Nihayah (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2013)
This articles contains the search of concepts of basyar and insan in the Qur’an include the meaning and context of use and the search for a correlation to kebasyariyyahan and kema’s u man of Prophet. This is because the authors found that the editor of the Qur’an in relation to prophetic mainly stating his humanity always use the word “basyar” not insan. Though both of these words by language experts have the same meaning, that is “human sense”. On the other side of the use of the word basyar to express humanity of the Prophet and the other apostles impact on the emergence of thoughts that reveal trends in humanity efforts of the Prophet in all aspects in common with other human beings and also restrictions on kema’su man of the Prophet. To answer these problems the author uses the method maudu’i to clarify and seek guidance verses of basyar and insa n in the whole of the Koran as well as analyzing and looking for correlation to kebasyariyyahan and kema’s u man of the Messenger saw that in this case the author uses descriptive analytical method.The results showed that there was the difference between basyar and insan, so the impact on inequality in the person of the Prophet with other human beings in all aspects ( the similarities are limited to matters related to instinct, function and physical needs)